Contextualising Diasporic Identity In Vikram Seth’s Mappings (Journal of Namibian Studies : History Politics Culture, 2023)
This paper explores how Vikram Seth’s diasporic identity and its features are highlighted throughout the collection, Mappings. Mappings writes in an autobiographical voice, and many of his poems employ the first-person narrative style. The author’s experiences and emotions are clearly expressed in the collection. In many of his poetry, alienation and nostalgia are the main topics. This collection of his poetry highlights his ideas and sentiments around family and the conflicts between the events of the past and the present. The collection’s opening poetry, written by Seth himself, is likewise autobiographical and centres on the psychological and cultural struggle that separates his native India from the United States, where he has been residing for many years. Despite his classical training, he writes in a modern style that incorporates free-verse, personal accounts of immigration and movement, and other similar modern elements.